Factor H Autoantibodies and Complement-Mediated Diseases - Zhang, Yuzhou; Ghiringhelli Borsa, Nicolo; Shao, Dingwu; Dopler, Arthur; Jones, Michael B.; Meyer, Nicole C.; Pitcher, Gabriella R.; Taylor, Amanda O.; Nester, Carla M.; Schmidt, Christoph Q.; Smith, Richard J. H. (Frontiers in Immunology, 2020)
Factor H (FH), a member of the regulators-of-complement-activation (RCA) family of proteins, circulates in human plasma at concentrations of 180-420 mg/L where it controls the alternative pathway (AP) of complement in the fluid phase and on cell surfaces. When the regulatory function of FH is impaired, complement-mediated tissue injury and inflammation occur, leading to diseases such as atypical hemolytic uremic syndrome (a thrombotic microangiopathy or TMA), C3 glomerulopathy (C3G) and monoclonal gammopathy of renal significance (MGRS). A pathophysiological cause of compromised FH function is the development of autoantibodies to various domains of the FH protein. FH autoantibodies (FHAAs) are identified in up to 10% of patients with aHUS, ~3% of patients with C3G, and rarely in patients with MGRS. The phenotypic variability of FHAA-mediated disease reflects both the complexity of FH and the epitope specificity of FHAA for select regions of the native protein. In this paper, we have characterized FHAA epitopes in a large cohort of patients diagnosed with TMA, C3G or MGRS. We explore the epitopes recognized by FHAAs in these diseases and the association of FHAAs with the genetic deletion of both copies of the CFHR1 gene to show how these disease phenotypes are associated with this diverse spectrum of autoantibodies.